Orientation Contrast and Entropy Contrast in the Genesis of Subjective Contours along Thin Lines. (January 2014) - Gillam, Barbara J; Wardle, Susan G; Vecellio, Elia
Subjective contours are widely considered to be an aspect of the perception of occlusion, but considerations of occlusion do not always drive predictions of their strength. Occluding surfaces have no necessary relationship to the contours they occlude, yet it is commonly predicted that subjective contours will be strongest for inducer alignments that are orthogonal to inducer orientations. In several papers we have proposed that a lack of relationship between inducers and their alignment promotes seeing subjective contours. We explore this further here using horizontal or near-horizontal thin-line inducers arranged vertically with linearly aligned terminations along central gaps. Subjective contour strength was measured using the method of paired comparison in two experiments. The weakest subjective contours were found when the gap was orthogonal to the inducers and parallel to the outer edges of the line set. Subjective contours were strengthened by orientation contrast, defined either as a nonorthogonal relationship between the gap and the inducers or as nonparallelism between the gap and the outer alignments of the inducers. The effect was replicated at both high and low line densities. We also confirmed a strong effect of high inducer entropy ( variations in inducer orientation and separation) with thin-line inducers. The results support the view that the lack of a relationship of alignments to what is aligned is a major determinant of subjective contour strength.